2020
DOI: 10.1109/access.2020.2990410
|View full text |Cite
|
Sign up to set email alerts
|

Target Tracking Method Based on Adaptive Structured Sparse Representation With Attention

Abstract: Considering the problems of motion blur, partial occlusion and fast motion in target tracking, a target tracking method based on adaptive structured sparse representation with attention is proposed. Under the framework of particle filtering, the performance of high-quality templates is enhanced through an attention mechanism. Structure sparseness is used to build candidate target sets and sparse models between candidate samples and local patches of target templates. Combined with the sparse residual method, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Based on different issues of the scene complexity, different methods of tracking have been proposed in literature such as feature-based tracking [7][8][9][10], model-based tracking [11][12][13][14][15][16][17], region-based tracking [18], and deformable template-based tracking [19][20][21]. It has been observed that particle filter in feature space provides a clear understanding and effective analysis of the target object in a scene.…”
Section: Introductionmentioning
confidence: 99%
“…Based on different issues of the scene complexity, different methods of tracking have been proposed in literature such as feature-based tracking [7][8][9][10], model-based tracking [11][12][13][14][15][16][17], region-based tracking [18], and deformable template-based tracking [19][20][21]. It has been observed that particle filter in feature space provides a clear understanding and effective analysis of the target object in a scene.…”
Section: Introductionmentioning
confidence: 99%